HUBUNGAN KEMAMPUAN MANAJEMEN STRES DENGAN TINGKAT STRES PADA ORANGTUA ANAK TUNAGRAHITA DI SLBN 1 PALANGKARAYA - Dewi Apriliyanti; Desti Anugrahni; Vina Agustina (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin, 2018)
The Parent who had children mental retardation bibliography will experienced a variety of challenges different compared to that have children normal. Various sources stress that had come upon them of contrasted with a old in general. This research using design research correlational to a draft this research is the cross sectional technique sampling use simple random sampling. Sample in this research was 52 parents children mental retardation bibliography in SLBN 1 Palangka Raya. The result on statistical tests showed Spearman Rank test statistics show the value of significancy P value α < significancy α = 0.05. The value of using Spearman Rank obtained in the Sig (2-tailed) of 0.001. There was some a significant relation exists between management capability of stress by the level of the stress. A solution to deal with parents who subjected to stress, namely must can keep up his or her being subjected to stress and performs actions appropriate to the principles of stress management in order that it may produce a positive coping.